Play as a mechanism of working through medical trauma for children with medical illnesses and their siblings. (September 2013) - Nabors, Laura; Bartz, Jennifer; Kichler, Jessica; Sievers, Rebecca; Elkins, Rebecca; Pangallo, Jordan
<x xml:space="preserve">Abstract</x> Children's reactions to medical trauma have been recorded through play. In this study, participants were 15 children with medical illnesses, 14 siblings of children with a medical illness, and 6 children in the community who did not have any ill family members. Children participated in play groups and their play with medical toys was videotaped and coded for themes that would provide a window on their perspectives. The play of children with medical illnesses and siblings was similar. Medical play was a mechanism for imaginal coping and working through stress related to medical experiences. In contrast, children in the comparison group did not engage in much medical play and when they did, they did not demonstrate a rich play experience with detailed medical stories. Future research should focus on ways to use play therapy techniques to help medically ill children and their siblings cope with their feelings and reactions to medical events related to chronic illness.